The Effectiveness of Environmental Policy Mix: Evidence from the Zhejiang Sewage Treatment Policy - Peng Wu; Huifang Cheng; Hongyi Li (Discrete Dynamics in Nature and Society)
The development of more effective environmental policies is a common concern among scholars, government and the public. This paper attempts to investigate whether the environmental policy mix can really work. Taking the “Five Water Co-Treatment” policy of Zhejiang Province as an example, we applied the synthetic control method to examine the impact of multi-objective environmental policies on industrial sewage discharge and urban sewage discharge in Zhejiang. Further, we analyzed the effect of industrial value added and the length of water pipelines on sewage discharge and examined the potential environmental Kuznets curve (EKC) relationships. Our results of synthetic control imply that the “Five Water Co-Treatment” policy has increased the industrial and urban sewage discharge. However, the results of the extended analysis show that this is a process of standardizing sewage discharge and an embodiment of enhanced sewage treatment capacity. Therefore, we believe that the “Five Water Co-Treatment” policy is effective and should continue to advance.